How does toxoplasmosis affect the maternal‐foetal immune interface and pregnancy?. (19th December 2018) - Borges, Margarida; Magalhães Silva, Tânia; Brito, Carina; Teixeira, Natércia; Roberts, Craig W.
Summary: Toxoplasma gondii is a zoonotic parasite which, depending on the geographical location, can infect between 10% and 90% of humans. Infection during pregnancy may result in congenital toxoplasmosis. The effects on the foetus vary depending on the stage of gestation in which primary maternal infection arises. A large body of research has focused on understanding immune response to toxoplasmosis, although few studies have addressed how it is affected by pregnancy or the pathological consequences of infection at the maternal‐foetal interface. There is a lack of knowledge about how maternal immune cells, specifically macrophages, are modulated during infection and the resulting consequences for parasite control and pathology. Herein, we discuss the potential of T. gondii infection to affect the maternal‐foetal interface and the potential of pregnancy to disrupt maternal immunity to T. gondii infection.